La catechesi figurata dei mosaici della chiesa del vescovo Sergio ad Umm al-Rasas di Giordania - Gautier, E. (Liber Annuus, 2000)
Abstract The archaeological findings of the ecclesiastical complex of St. Stephen at Umm el Rasas (Kastron Mefaa) in Trans Jordan, have brought to light two separate churches with floor mosaics of the highest quality made by artisans of the Madaba school. The numerous figures depicted are still visible and preserved rather well in spite of partial destruction by iconophobes. The oldest church, so called of Bishop Sergio (587 AD), displays a carpet of mosaics with a deep symbolical meaning which can be interpreted through the homilies of Cyril and John, both bishops of Jerusalem at the end of the IV century. Represented are symbols of universal meaning to the Church: the earth with its fruits, grapes, symbolic animals: lambs, lions, peacocks, bulls. A pattern frequently met in Trans – Jordanian churches, which in this case conveys a stronger meaning, like the phoenix with the head surrounded by a nimbus with eight rays; a number referring to the Resurrection. The most characteristic element of this iconographical program are the strikingly vibrant scenes of everyday life: a man carrying his own bed remind the Bethesda miracle (Jn 5, 1-9; Mt 9, 1-8, Mk 2, 3- 12, Lk 5, 18-26) and the call of Cyril to his faithful herd to avoid sins. A man carried his son on his shoulders and indicates him the church, the shepherd. These are pictures of strong catechetical meaning, which can be traced to the preaching of the two bishops of Jerusalem.